Validation of a radiosonde‐based cloud layer detection method against a ground‐based remote sensing method at multiple ARM sites. Issue 2 (31st January 2013) - Zhang, Jinqiang; Li, Zhanqing; Chen, Hongbin; Cribb, Maureen
Abstract : [1] Cloud vertical structure is a key quantity in meteorological and climate studies, but it is also among the most difficult quantities to observe. In this study, we develop a long‐term (10 years) radiosonde‐based cloud profile product for the U.S. Department of Energy's Atmospheric Radiation Measurement (ARM) program Southern Great Plains (SGP), Tropical Western Pacific (TWP), and North Slope of Alaska (NSA) sites and a shorter‐term product for the ARM Mobile Facility (AMF) deployed in Shouxian, Anhui Province, China (AMF‐China). The AMF‐China site was in operation from 14 May to 28 December 2008; the ARM sites have been collecting data for over 15 years. The Active Remote Sensing of Cloud (ARSCL) value‐added product (VAP), which combines data from the 95‐GHz W‐band ARM Cloud Radar (WACR) and/or the 35‐GHz Millimeter Microwave Cloud Radar (MMCR), is used in this study to validate the radiosonde‐based cloud layer retrieval method. The performance of the radiosonde‐based cloud layer retrieval method applied to data from different climate regimes is evaluated. Overall, cloud layers derived from the ARSCL VAP and radiosonde data agree very well at the SGP and AMF‐China sites. At the TWP and NSA sites, the radiosonde tends to detect more cloud layers in the upper troposphere. Key Points: [2] Radiosonde data can be used to portray cloud vertical structure The radiosonde‐based cloud layer retrieval method is validated Radiosonde approach matches with remote sensing approach